COSMIC RAY INTENSITY VARIATIONS DURING 1962 - Sandstrom,A.E.; Dyring,E.; Ekstrom,L.; Gronkvist,B.O.; Lindgren,AND S. (1963)
A detailed account is given of the diurnal and semidiurnal variation recorded in Uppsala and Kiruna by a neutron monitor, two cubical tele scopes and six inclined telescopes. Six de creases that took place are illustrated by bi hourly diagrams. The diurnal variation is il lustrated by a number of vector sum diagrams for sun rotation periods. For the diurnal vari ation recorded by part of our instruments a rather abrupt phase shift to later hours seems to have occurred in the autumn. (Author)